To Study Factors Affecting Surgical Outcomes Of Congenital Diaphragmatic Hernia Repair In Pediatric Patients - Sharma, Pramila; J Baindur, Aditya; Mathur, Geetika; Goyal, Pankaj; Gupta, Rashmi; Kumar Chopra, Ashok (Journal of Neonatal Surgery, 2025)
Introduction- Congenital diaphragmatic hernia (CDH) is a challenging and potentially life-threatening congenital anomaly that occurs in neonates. The management of CDH requires a multidisciplinary approach, including prenatal diagnosis, neonatal intensive care, and surgical intervention. Major differences in physiology between neonates and adults makes the former group more liable to morbidity and mortality. Risk estimation in these neonates helps to counsel parents about the post operative outcomes. Aim: - To analyse the potential risk factors affecting the surgical outcome in neonates undergoing CDH repair in our tertiery health care setup. Material and Methods: This is a retrospective and prospective study done from January 2023 to january 2025, total 124 neonates who underwent CDH repair over a period of 2 years. Demographic data and clinical and laboratory parameters at admission were recorded in a proforma. Pre-operative, intra-operative and post-operative adverse events were observed and recorded. Various factors were subjected to tests of significance and a further multivariate analysis was done to assess the significance of the independent variables in predicting the final surgical outcome. Results: out of 124 patients 91 neonates were discharged successfully, with mortality noted in 34 patients (27.2%). Gestational age, weight at admission and associated congenital anomalies affected the post-operative outcome significantly. Pre-operative persistent pulmonary hypertension (PPHN), need for transfusion of blood products, inotropic and respiratory support correlated with adverse post-operative outcomes. Similarly, post-operative mortality was noted to be higher in the neonates who required re-intubation, post-operative transfusion of blood products, surgical site infection or ventilator associated pneumonia (VAP). Conclusion: from this study we concluded that Low birth weight, associated congenital anomalies, PPHN, need for transfusion of blood products, need for inotropes and mechanical ventilation, wound infection and duration of hospital stay are various factors that significantly influence the surgical outcome in CDH repair. Identification of such potential prognostic factors not only helps in improving the surgical outcome in these neonates, but also helps in prognostication and appropriate counselling of the parents.